Karakterisasi Produk Yoghurt Susu Nabati Kacang Arbila (Phaseolus lunatus L.) - Nalu, Fitrian Narti Hona; Ledo, Mellisa Erlyn; Solle, Hartini Realista Lydia (Universitas Medan Area, 2021)
Arbila beans (Phaseolus lunatus L.) is one of the genetic resources of East Nusa Tenggara. It has not been optimally utilized. It is, therefore, necessary to produce food products that have good economic value to increase people's purchasing power. Yogurt is one of them. The purposes of this study were to determine the process of making yogurt from Arbila beans (Phaseolus lunatus L.), to obtain a profile of Arbila bean yogurt with the right composition, and to analyze its nutritional content, panelists' preference and safety for consumption observed from the coliform test results. The method used in this study was the experimental method carried out in four stages; 1) the making of Arbila bean yogurt in four treatments; Control (10% plain biocule), A1 (20% of plain biocule), A2 (30% of plain biocule), A3 (45% of plain biocule); 2) proximate test; 3) organoleptic test; 4) coliform test. The results of the proximate analysis indicated that the highest protein content of 4.32% was found in yogurt A3, while the highest carbohydrate content was 12.45% and the lowest fat was 0.32% in A1 yogurt. Organoleptic test results indicated that the highest preference for panelists in Arbila bean yogurt A3. Coliform test results showed negative results for the presence of Escherichia coli in all treatments. Therefore, Arbila bean yogurt with the composition of A3 (45% of plain biocule) is recommended as a good Nabati yogurt made of soya.